ANALYZING THE DYNAMICS OF CONTRACTOR FAILURES IN E-PROCUREMENT BASED CONSTRUCTION TENDERS: A CASE STUDY IN BANDA ACEH, INDONESIA (ASEAN Engineering Journal, 2025)
The inefficiencies in the e-procurement tender process have become a critical issue for government construction projects in Banda Aceh, Indonesia, leading to a high incidence of contractor failures. This research investigates the underlying factors contributing to these failures, aiming to identify the primary influences and their relative impacts. The study employs a comprehensive methodological approach, including descriptive analysis, factor analysis, and multiple linear regression analysis. Key findings reveal that administrative factors (X1) and qualification factors (X4) significantly contribute to contractor failures. However, the analysis shows that technical competence (X2) is the most influential factor. The regression analysis results in the equation Y = 5.213 + 0.797X1 + 1.061X2 + 0.609X3 + 0.280X4, with a coefficient of determination (R2) of 0.955. This indicates that 95.50% of the variability in contractor failure rates can be explained by the variables of administration, technical competence, pricing strategy, and qualification. This study contributes to a better understanding of contractor failures in e-procurement dynamics and provides actionable insights that can enhance the efficiency and success of future tender processes.